MICRO BUSINESS STUDY OF TRADITIONAL HEALTH DRINK PRODUCTS “TELANG LIMAO BANGKAK” (GREEN BUSINESS CANVAS STUDY “ECOCANVAS”) - Muhammad Alfarizi; Rini Kurnia Sari (University of Sultan Ageng Tirtayasa, 2021)
This study aims to formulate a business development strategy that is appropriate and can be applied to the traditional Indonesian health drink business